Sway Model for the Lateral Torsional Buckling Analysis of Wooden Twin-beam-deck Systems. (June 2019) - Du, Yang; Mohareb, Magdi; Doudak, Ghasan
Abstract: The present study develops a finite element model for the lateral torsional buckling analysis of wooden twin beams braced by deck boards subjected to gravity or wind uplift loading. The restraining action of the deck boards is modelled as continuous partial lateral and twist restraints provided at the top of both beams that capture the interaction between both beams. A parametric study is then conducted to examine the effects of beam and deck spans, load type, load height, lateral restraint height and stiffness and number of beam spans on the overall buckling capacity. The results indicate that the restraining effects of deck boards significantly improve the lateral torsional buckling capacity of twin-beam-deck assemblies.